Effect of Feeding Commercial Broiler Diets on Growth Performance of Tswana and Orpington Chickens Reared upto 18 Weeks of Age Under Intensive System - Radikara, Malebogo Virginia; Moreki , John Cassius; Mareko, Molebeledi Horatius Dambe; Kgwatalala, Patrick Monametsi (International Journal of Poultry Science, 2016)
Objective: This study was conducted to compare growth performance and carcass characteristics of Tswana and Orpington chickens. Methodology: A total of 120 day old chicks (60 Tswana and 60 Orpington) were randomly distributed to 4 replicates using a completely randomized design. Birds were raised under intensive system upto 18 weeks of age and fed commercial diets. Parameters recorded included feed intake, Body Weight (BW), Body Weight Gain (BWG), Feed Conversion Ratio (FCR), mortality, final live weight, dressed weight, dressing percentage and portions/primal cuts weight. Data were analyzed using the general linear model procedures in statistical analysis system (SAS). Results: There were no significant differences (p>0.05) in feed intake amongst the tested chicken lines. No significant sex differences (p>0.05) in BW between Orpington and Tswana chickens were observed. At 11 and 18 weeks of age BWG of Orpington males were significantly higher than Tswana males (135.58±8.00 and 132.74±8.51; 94.39±7.60 and 51.82±8.26, respectively). Males were significantly (p<0.05) heavier than their age-matched female counterparts. The FCR of Orpingtons was less than that of Tswana chickens. The highest mortality rate was recorded in Tswana chickens (8%) compared to Orpingtons (5%). At 18 weeks of age, the highest final live weight was recorded in Orpington (male 1862.74 g, female 1493.46 g) compared to Tswana chickens (male 1732.89 g, female 1467.90 g). Orpingtons had significantly (p<0.05) higher live weight, dressed weight, carcass weight and primal cuts weight compared to indigenous Tswana chickens. No differences (p>0.05) were observed for dressing percentage. Conclusion: These results imply that Orpingtons may be considered in future breed improvement programmes.